2022
DOI: 10.21009/1.08108
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Integrated Project-Based Learning Science Technology Engineering Mathematics on Creative Thinking Skills and Student Cognitive Learning Outcomes in Dynamic Fluid

Abstract: This study aims to determine the effect of implementing STEM-integrated PJBL on students' creative thinking skills and cognitive learning outcomes. This research is quasi-experimental with a two-group pretest-posttest design. The research population is all grade 11th IPA SMAN 3 Bungo students, and the sample was determined by random sampling. Three projects conducted by the students were water pump free energy, fountain free energy, and air bubble generator. Two instruments of creative thinking test in essay f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Previous study showed that STEM's up-skilling activities engaged students' mind by encouraged them in a processoriented measurement and evaluation [27]. Therefore, the implementation of inquiry-based STEM learning can support students in developing their critical thinking skills by exploring the understanding they already have to describe and understand the various stages of problems that lead to conclusions [28,29].…”
Section: Teacher : Why the Remote Car Can Run? Studentmentioning
confidence: 99%
“…Previous study showed that STEM's up-skilling activities engaged students' mind by encouraged them in a processoriented measurement and evaluation [27]. Therefore, the implementation of inquiry-based STEM learning can support students in developing their critical thinking skills by exploring the understanding they already have to describe and understand the various stages of problems that lead to conclusions [28,29].…”
Section: Teacher : Why the Remote Car Can Run? Studentmentioning
confidence: 99%
“…The creative thinking skills of students have an impact on science learning, particularly in physics. This is supported by research stating that through the process of creative thinking, students will construct their knowledge through learning experiences, thus improving physics learning outcomes [4]. Physics learning is also relevant to the real world and everyday life contexts, and it can utilize technology as a learning tool.…”
Section: Introductionmentioning
confidence: 97%
“…The industrial revolution 4.0 and the rapid evolution of technology have had an impact on the implementation of 21st century education. Education requires 4C abilities, namely critical thinking and problem solving, collaboration, creativity and innovation, as well as communication skills that prepare human resources (HR) to compete globally (Sinurat et al, 2022;Yennita et al, 2021). Based on the 2013 curriculum, it requires learning that can develop students' mindsets to find solutions to every problem with a scientific process.…”
Section: Introductionmentioning
confidence: 99%